DETERMINING GENETIC DIVERGENCE AMONG Brassica rapa ECOTYPES THROUGH ELECTROPHORETIC MOBILITY OF TOTAL SEED PROTEINS - S. A. Jan; Z. K. Shinwari; M. A. Rabbani (Journal of Animal and Plant Sciences, 2016)
Estimation of total seed proteins based variation among different Brassica rapa ecotypes is important for crop improvement and efficient utilization. In the present study, variations in total seed proteins among three ecotypes of B. rapa (brown sarson, yellow sarson and toria) were studied. Twenty different genotypes from all the ecotypes were analysed through SDS-PAGE and their phylogenetic relation was recorded. The polymorphism in protein size was investigated and they were divided into four main groups on the basis of molecular weight ranging from ~10 kDa to ~180 kDa. Group A comprised of large size proteins (~136 kDa to ~180 kDa), group D consisted of small size proteins (~10 kDa to ~19 kDa) whereas group B and C consisted of medium sized proteins (~26 kDa to ~115 kDa). The data of total soluble seed protein based variations were analysed through Unweighted Pair Group Method with Arithmetic Mean (UPGMA), which clustered all three ecotypes into four main groups. The cluster I and III contained one toria and brown sarson genotypes, respectively. These two groups showed maximum polymorphism as compared to other cluster groups. The clusters III and IV had all three ecotypes. The similarity coefficient values ranging from 47 to 100% were also recorded for all three types. The maximum similarity coefficient value was recorded as 100% for brown sarson and toria genotypes while the least similarity indices was recorded for brown sarson and yellow sarson ecotypes i.e. 47%. For the first time, we have reported considerable protein based variations in all three ecotypes of B. rapa. Our findings will be helpful as a preliminary study on the characterization of B.  rapa ecotypes.
Keywords: B. rapa; crop improvement; protein based diversity; phylogenetic relation